The Emphatic Imagery: A Study in Dickinson's Narrative of Time, Life and Death - Ibraheeh Dawood(Ph.D.), Lecturer: Imad; Musa Mohammed, Lecturer: Omran (مجلة كلية التربية, 2021)
Emily Dickinson is of those woman poets who in their time said something for few or no listeners till it was too late to rediscover what she actually meant. The early transcendentalists of 19th century America eclipsed her significance for a while. In this, she has to accept the lot of a woman trying to be an artist in the midst of a masculine-oriented mainstream culture. However, Dickinson is so prolific a writer that a reader cannot help stopping at her shelves to explore the meanings she had left in between the lines of her poems. Like other poets and thinkers of her time, Dickinson tried her best to draw a philosophical narrative of her own. That was a universal narrative rather than a mere personal complain or discomfort. In addition to her particular understanding of the questions of time, life and death, she also excelled in revealing a linguistic skill that only Wallace Stevens later perfected in a much critical way. As she grew older and abler in her artistic experience, her poetry grew much more mystic, religious and philosophical too. Behind the simplicity of the utterance and the clarity of the image, she wrapped her words with unfathomable meaning that frequently requires a critical taste to arrive at its significance; a depth of meaning and a wide array of symbolism.
Keywords: The